Contralateral Keyhole Biportal Endoscopic Surgery for Ruptured Lumbar Herniated Disc: A Technical Feasibility and Early Clinical Outcomes - Jung Hoon Park; Jae Won Jang; Woo Min Park; Cheul Woong Park (Neurospine, 2020)
Objective Spinal endoscopic surgery is increasingly adapted as a minimal invasive technique, however, significant facet joint violation may be developed after ipsilateral laminectomy. The aim of this study is to introduce surgical technique of contralateral keyhole biportal endoscopic surgery (CKES) for ruptured lumbar disc and report it is early surgical outcomes with facet joint violation. Methods Between January to December 2019, 27 patients with ruptured lumbar disc were underwent CKES. Simple radiographs were obtained to investigate development of iatrogenic instability or spondylolisthesis. Magnetic resonance imaging scan was checked about 8 hours after surgery to evaluate successful removal of ruptured disc and existence of facet joint violation. Clinical outcomes were assessed by modified MacNab criteria, visual analogue scale (VAS) scores of back and radicular pain. Results The mean age of the patients was 62.8 ± 12.48 years. The average operative time and mean follow-up period were 57.1 ± 21.36 minutes and 8.1 ± 3.78 months, respectively. Compared to preoperative scores, the VAS scores of back and radicular pain were significantly improved. Modified MacNab outcome grade was good to excellent in 96.3% (26 out of 27 patients) of patients. The reduction rate of facet joint plane was about 4.9% after contralateral approach. Conclusion CKES may be considered as an excellent surgical option to treat ruptured lumbar disc without the development of iatrogenic instability. Low rate of facet joint reduction, good visualization of lateral recess, and identification of accurate midline of central spinal canal are advantages of the procedure.